Kinetics of crystal nucleation in ionic solutions: Electrostatics and hydration forces - Kowacz, M.; Prieto, M.; Putnis, Andrew (Pergamon, 2010)
The heat of precipitation, the mean crystal size and the broadness of crystal size distribution of barium sulfate precipitating in aqueous solutions of different background electrolytes (KCl, NaCl, LiCl, NaBr or NaF), was shown to vary at constant thermodynamic driving force (supersaturation) and constant ionic strength depending on the salt present in solution. The relative inversion in the effect of respective background ions on the characteristics of barite precipitate was observed between two studied supersaturation (O) and ionic strength (IS) conditions. The crystal size variance (ß2) increased in the presence of background electrolytes in the order LiCl < NaCl < KCl at O = 103.33 and IS = 0.03 M and KCl < NaCl < LiCl at O = 103.77 and IS = 0.09 M. At a given O and IS the respective size of barite crystals decreased with increasing ß2 in chloride salts of different cations and remained constant in sodium salts of different anions. We suggest that ionic salts affect the kinetics of barite nucleation and growth due to their influence on water of solvation and bulk solvent structure. This idea is consistent with the hypothesis that the kinetic barrier for barium sulfate nucleation depends on the frequency of water exchange around respective building units that can be modified by additives present in solution. In electrolyte solution the relative switchover between long range electrostatic interactions and short range hydration forces, which influence the dynamics of solvent exchange between an ion solvation shell and bulk fluid, results in the observed inversion in the effect of differently hydrated salts on nucleation rates and the resulting precipitate characteristics. © 2009 Elsevier Ltd. All rights reserved.